Help-seeking for mental health problems by employees in the Australian Mining Industry. Issue 1 (December 2016) - Tynan, Ross; Considine, Robyn; Rich, Jane; Skehan, Jaelea; Wiggers, John; Lewin, Terry; James, Carole; Inder, Kerry; Baker, Amanda; Kay-Lambkin, Frances; Perkins, David; Kelly, Brian
Abstract Background The current study examined help-seeking behavior for mental health problems of employees in the mining industry. Methods The research involved a paper-based survey completed by a cross-section of employees from eight coalmine sites. The research aimed to investigate the frequency of contact with professional and non-professional sources of support, and to determine the socio-demographic and workplace factors associated. Results A total of 1, 457 employees participated, of which, 46.6 % of participants reported contact with support to discuss their own mental health within the preceding 12 months. Hierarchical logistic regression revealed a significant contribution of workplace variables, with job security and satisfaction with work significantly associated with help-seeking behavior. Conclusions The results provide an insight into the help-seeking behaviour of mining employees, providing useful information to guide mental health workplace program development for the mining industry, and male-dominated industry more broadly.